Does financial development and economic growth promote employment in Nigeria? - Ololade, Babatunde Moses; Olabisi, Olabode Eric (Journal of Empirical Studies, 2023)
In most African countries, including Nigeria, employment generation has been a major challenge that poses a serious issue for the economic well-being of the people. Therefore, the aim of this paper is to investigate whether financial development and economic growth promote employment generation in Nigeria, covering 1999–2020. To investigate the relationship among financial development, economic growth, and employment in Nigeria, the Autoregressive Distributed Lags (ARDL) bound-testing estimation method was employed. This approach allows level I(0) and first difference I(1) macroeconomic data to be estimated without bias. It also offers the possibility of computing the dynamic error correction model (ECM). Our findings show a long-run relationship among financial development, employment rate, inflation rate, and economic growth in Nigeria. The result further shows that inflation has a negative and significant relationship with the employment rate. Also, financial development reveals a positive and significant relationship with employment. The result further shows that economic growth promotes employment in Nigeria. Following the results of our analysis, this study recommends, among other things, policy formulations on expansionary monetary policies that will ensure the availability of credits for the private sector. Also, stock market listing requirements for small and medium-sized businesses should be friendly to encourage small and medium-sized enterprises (SMEs) to list for access to finance. Also, policies that will drastically reduce the high rate of inflation should be implemented.